Kematangan Beragama Masyarakat Industri Batik - Tri Astutik Haryati (Jurnal Penelitian, 2016)
This article determines the the attitude of society in Pekalongan batik industry with regard to predictors of confidence in their perceptions of the pillars of faith and religious activities. By using the quantitative research approach, the result of research: first, the belief in the pillars of faith affect only 10.8%, so the result was not significant; second, the perception of religious activity affects at 18.5%, so the results are significant; and third, the belief on the pillars of faith and perception of the religious activities collectively contributed 23.6%. So the latest result is significant.